Pengembangan trainer robot line follower dan revitalisasi pembelajaran abad 21 menuju era society 5.0 di SMK Negeri 1 Kras Kediri - Sujito Sujito; Siti Sendari; Hakkun Elmunsyah; Mahfud Jiono; Rindi Santika Agustin; Muhammad Tahfidlul Azmi (Unri Conference Series: Community Engagement, 2021)
To support industrial development in the era of super-smart society 5.0, the State Vocational High School 1 Kras Kediri seeks to produce competent graduates by applying a teaching model that has a constructive paradigm, involves the active role of students, and prioritizes practicum. It is intended that SMK graduates can compete in the 21st-century industry. The problem of schools today is the lack of complete learning support equipment. So that learning is less effective. On the other hand, the implementation of learning is still dominated by a teacher-oriented learning system. So to support the Computer Network Engineering skill competency program in basic programming subjects, a Line Follower Robot Trainer was developed. The Line Follower Robot Trainer that has been made has sophisticated specifications using an ESP32 microcontroller processor. In addition, 21st-century learning revitalization workshops were also conducted which were attended by teachers of SMK Negeri 1 Kras Kediri to strengthen the 21st-century learning paradigm based on students (student-oriented learning). In general, the results of the community service program that have been implemented can overcome the problems faced by SMK Negeri 1 Kras, the Computer Engineering expertise program in programming subjects.